EFFECTIVENESS OF THE ROLE OF HALAL PRODUCT PROCESS COMPANION IN THE FREE HALAL CERTIFICATION SCHEME (SEHATI) IN A MULTICULTURAL SOCIETY FOR INDEPENDENT CLAIM BUSINESSES - Dwi Lestari, Wiwit; Azis, Abdul; Hakim, Lukman (Universitas Islam Malang, 2024)
The government, through the Halal Product Assurance Organizing Agency, issued a regulation on the obligation of halal certification for micro and small businesses. Halal Product Process Assistance (PPH) is aimed at helping MSME actors in Banyuwangi Regency. The Free Halal Certification Program (SEHATI) is a free program offered by the Ministry of Religious Affairs of the Republic of Indonesia through BPJPH. The program is one of the strategies for accelerating the increase in halal-certified MSME actors in Indonesia. This study aims to understand the role of halal product process companions and evaluate the effectiveness of their performance in increasing halal understanding and awareness among business actors related to halal certification. The data collection techniques used are observation, interviews, and documentation. Data analysis is done through data reduction and presentation, and conclusions are drawn. In order to realize the effectiveness of assistance, halal product process companions have implemented several methods. From various efforts that have been made, a result was found where halal awareness of business actors has been formed, as evidenced by the behaviour of business actors in choosing production materials that are guaranteed halal, production processes that are by Sharia, and the willingness to provide halal guarantees on the products produced.